2017
DOI: 10.5194/bg-14-989-2017
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic versus biotic controls on soil nitrogen cycling in drylands along a 3200 km transect

Abstract: Nitrogen (N) cycling in drylands under changing climate is not well understood. Our understanding of N cycling over larger scales to date relies heavily on the measurement of bulk soil N, and the information about internal soil N transformations remains limited. The 15 N natural abundance (δ 15 N) of ammonium and nitrate can serve as a proxy record for the N processes in soils. To better understand the patterns and mechanisms of N cycling in drylands, we collected soils along a 3200 km transect at about 100 km… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Species that prefer nitrate relative to ammonium generally have lower δ 15 N values than species that prefer ammonium (Houlton et al 2007). In our previous study along the same climatic gradient, we found that δ 15 N values of ammonium consistently increased, while δ 15 N values of nitrate increased first and then decreased with increasing aridity (see Liu et al 2017). These results suggest a shift of dominant inorganic N sources for plants with aridity, resulting in a positive relationship between aridity and plant δ 15 N values and a decoupled relationship between plant and soil bulk δ 15 N values.…”
Section: N Stable Isotopes In Plants Along the Aridity Gradientmentioning
confidence: 64%
“…Species that prefer nitrate relative to ammonium generally have lower δ 15 N values than species that prefer ammonium (Houlton et al 2007). In our previous study along the same climatic gradient, we found that δ 15 N values of ammonium consistently increased, while δ 15 N values of nitrate increased first and then decreased with increasing aridity (see Liu et al 2017). These results suggest a shift of dominant inorganic N sources for plants with aridity, resulting in a positive relationship between aridity and plant δ 15 N values and a decoupled relationship between plant and soil bulk δ 15 N values.…”
Section: N Stable Isotopes In Plants Along the Aridity Gradientmentioning
confidence: 64%
“…Although the intensity of the competition between abiotic and microbial reactions depends on environmental factors (e.g. temperature, coexisting chemical substances, water availability and pH) (Melton et al ; Liu et al ), we have assumed that microbial reactions occur much faster than non‐biological reactions and so we have neglected the latter.…”
Section: The Model For Two Chemotrophs Catalysing the Sequential Catamentioning
confidence: 99%
“…The KCl extract was analyzed immediately for NH4-N and NO3-N concentrations using a Lachat Flow Injection Analyzer (AutoAnalyzer3-AA3, Seal Analytical, Mequon, WI) (Kachurina et al, 2000). In order to identify the sources of accumulated nitrate, the isotope compositions of nitrate (δ 15 N and δ 18 O) were analyzed based on the isotopic analysis of the produced N2O from NO3-N (Liu et al, 2017). The value is expressed as:…”
Section: Analyses Of Loess Physicochemical Properties and Isotopementioning
confidence: 99%